Peran Mahasiswa KKN di Nagari Simalanggang dalam Meningkatkan Karakter Remaja melalui Sosialisasi Bahaya NAPZA (Narkotika, Psikotropika, dan Zat Adiktif lainnya) - Indra Yeni; Dinda Puspita Riny; Annisa Fitri; Ulfa Dwi Maysarah; Vena Meldy; M. Abid Firjatullah Rikit (CV. ITTC INDONESIA, 2025)
Real Work Lectures (KKN) as a form of community service are vital for teaching young people about the risks associated with drug abuse (NAPZA). The research centers on an awareness campaign designed to highlight how social surroundings can shape teenagers' tendencies toward substance misuse. It delves into explanations of what drug abuse entails, its various forms, the consequences it brings, and methods to avoid it. To investigate how the initiative unfolded, a qualitative case study approach was employed, targeting two middle schools in Simalanggang. Information was collected via awareness sessions, direct involvement in observations, and record-keeping. The findings indicate that participants gained a deep grasp of NAPZA issues and practical ways to counteract them, while the campaign effectively inspired them to build better personal qualities.